(untitled) (Journal of Physical Education (Maringá), 2017)
The purpose was to analyze the effect of the ingestion of two amounts of water in the autonomic modulation. A total of 26 men aged 18–30 years under went 2 days of intervention and evaluation with 24 hours in between. The protocol consisted of the intake of 250 or 500 mL of water in a random order. To assess the initial transient HR during dynamic exercise, the cardiac vagal index was obtained using a 4-second exercise test during the pre- and post-ingestion periods (5, 10, 20, and 30 minutes). To evaluate autonomic modulation at home, HRV value 30 minutes after water intake was used when HR at rest was registered. The results shows: Five minutes after the water intake, the initial transient HR was increased (p = 0.02) with no difference in effect of the ingested volumes of water (p = 0.8). In HRV, there was no difference between the intake volumes in the time or frequency domains. There were differences in HR rest after 20 minutes compared to at other times (p < 0.05). In conclusion the results showed no difference in initial transient HR, HRV, or HR rest after the intake of 250 versus 500 mL of room temperature water in healthy individuals. However, resting initial transient HR and HR rest values differed among the analyzed times.